Sistem Monitoring Indeks Pencemaran Air Berbasis Internet of Things - Asharullah, Asharullah; Zainal, Muhammad; Jabbar, A. Abd. (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2026)
The coastal waters of Parepare City are surrounded by numerous food stalls whose wastewater and food residues are often discharged directly into the marine environment, leading to seawater pollution. Continuous monitoring is therefore required to assess water quality and support effective environmental management. This study aims to develop an Internet of Things (IoT)-based web server system for monitoring the seawater pollution index in the coastal waters of Parepare City. The research adopts a quantitative Research and Development (R&D) approach by integrating pH, turbidity, and Total Dissolved Solids (TDS) sensors to collect real-time water quality data. Sensor readings are transmitted to an IoT-based web server and processed to calculate the Water Pollution Index (WPI). Experimental results demonstrate that the system operates effectively under field conditions. Morning measurements produced a pH value of 6.9, turbidity of 2443 NTU, and TDS of 1179.1 ppm, resulting in a pollution index of 1.91, classified as lightly polluted. Afternoon measurements indicated a pollution index of 2.04 with increased turbidity, which also falls within the lightly polluted category. The proposed system provides a reliable solution for real-time monitoring of seawater quality in the coastal waters of Parepare City.